2012
DOI: 10.1038/onc.2012.461
|View full text |Cite
|
Sign up to set email alerts
|

NANOG modulates stemness in human colorectal cancer

Abstract: NANOG is a stem cell transcription factor that is essential for embryonic development, reprogramming normal adult cells and malignant transformation and progression. The nearly identical retrogene NANOGP8 is expressed in multiple cancers, but generally not in normal tissues and its function is not well defined. Our postulate is that NANOGP8 directly modulates the stemness of individual human colorectal carcinoma (CRC) cells. Stemness was measured in vitro as the spherogenicity of single CRC cells in serum free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
113
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(120 citation statements)
references
References 54 publications
(73 reference statements)
6
113
0
1
Order By: Relevance
“…4). Several preceding studies have argued that some CSC properties, such as enhanced tumorigenicity, may be inducible (5)(6)(7). However, these reports did not show whether these cells have the ability to differentiate into specific types of cancer tissues.…”
Section: Introductionmentioning
confidence: 42%
“…4). Several preceding studies have argued that some CSC properties, such as enhanced tumorigenicity, may be inducible (5)(6)(7). However, these reports did not show whether these cells have the ability to differentiate into specific types of cancer tissues.…”
Section: Introductionmentioning
confidence: 42%
“…Previous studies have shown that NANOG plays key roles in maintenance of CSCs stemness [32]. We thus hypothesized that NANOG might play an important role in aspirin-induced CSCs stemness suppression.…”
Section: Resultsmentioning
confidence: 99%
“…We detected the expression level of several stemness factors, including c-Myc, OCT4, NANOG and SOX2 [32, 41-43] by western blotting. Aspirin suppressed the stemness factors expression with increasing dose (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The over-expression of Nanog in hESC has been demonstrated to contribute to the maintenance of the undifferentiated state in the absence of feeders or conditioned media for a period of time 89 . Interestingly the expression of Nanog has also been found in several neoplasia 90,91 and was reported to improve proliferation and life span together with Oct-4 in human mesenchymal stem cells over-expressing these two transcription factors 92 .…”
Section: The Establishment and Improvement Of Culture Conditions Of Hescmentioning
confidence: 99%